Active expiration reduces hypercapnia in lung failure – results of the prospective interventional ActiveEx study and development of a prototype device for automated application - Denis Witham; Julius Valentin Kunz; Ann-Christin Krebs; Karoline Brückner; Roland Körner; Mareen Pigorsch; Kai-Uwe Eckardt; Paul Uwe Thamsen; Philipp Enghard; Julija Peter (PLoS ONE, 2025)
Background This study investigates the efficacy of Intermittent Abdominal Pressure Ventilation (IAPV) and Expiratory Rib Cage Compression (ERCC) in reducing hypercapnia among critically ill, mechanically ventilated patients. It also assesses the feasibility of automating these techniques using a self-developed, ventilator-synchronized device on a dummy. Methods This single-arm feasibility study was conducted in two intensive care units at Charité – Universitätsmedizin Berlin, including critically ill patients with hypercapnic lung failure, with additional lab testing at the Technical University of Berlin. Manual IAPV and ERCC were applied to patients, and automation feasibility was tested on a dummy using prototype device. Primary outcomes included changes in tidal volume and partial pressure of carbon dioxide (PaCO2) and device effectiveness at different PEEP levels. Results In nine hypercapnic patients, manual IAPV increased tidal volume from 5.72 to 8.85 mL/ kg predicted bodyweight (p < 0.001, relative effect (CI) 0.93 (0.79–1.06)) and ERCC from 5.79 to 8.13 mL/ kg predicted bodyweight (p < 0.001, relative effect (CI) 0.93 (0.80–1.05)). PaCO2 reduced after 20 minutes with both techniques (IAPV: from 65 to 52 mmHg, p < 0.01, relative effect (CI) 0.15 (0.01–0.28); ERCC: from 61 to 51 mmHg, p= < 0.01, relative effect (CI) 0.22 (0.07–0.37)). A transient decrease in oxygenation was fully and rapidly reversible. The automated device doubled tidal volumes in dummy simulations, with greater effectiveness at higher PEEP-levels. Conclusion Manual and automated ventilator-synchronized IAPV and ERCC were associated with improved ventilation. Their potential role in managing hypercapnic respiratory failure—such as in weaning failure, obstructive lung disease, or neuromuscular weakness—remains a subject for future clinical research. German Registry of Clinical Trials (DRKS00027397)